Cambridge Female Refuge Rules (1838-1844): An Institution for "Females Who Have Been Leading a Sinful Course of Life" - Romero-Ruiz, María Isabel (My University, 2019)
The Cambridge Female Refuge was an institution established in Cambridge Church Street in 1838 as a House of Mercy for the moral rescue of fallen women. Prostitution was a serious preoccupation at the time for both town and gown authorities. The University of Cambridge had its own regulations and female prison --the Spinning House -- to avoid promiscuity among students and the spread of venereal disease. The town authorities were also involved in the control of the trade in the areas under their jurisdiction. In this setting, this place was conceived as a refuge for women to return to the path of virtue and to be provided with proper employment at the beginning of the Victorian period . The aim was to instruct them religiously and morally to return them to their families and friends. In this sense, the aim of this paper is to demonstrate how the rules of the Cambridge Female Refuge reflect the ideology of containment and control of working-class women and the role of the local prominent classes and University authorities in philanthropy work that would mainly serve their interests. At the same time and following Judith Butler’s and Sarah Bracke’s theories, issues of vulnerability as well as of resilience and resistance concerning the inmates of the instituiton will be discussed in the light of archival sources.
Keywords: Prostitución - Aspectos sociales - Gran Bretaña - S.XIX; Cambridge, female refuge, rules, fallen women, vicotrian